Dynamic strength index: relationships with common performance variables and contextualization of training recommendations - Suchomel, T. J.; Sole, C. J.; Bellon, C. R.; Stone, M. H. (Journal of Human Kinetics, 2020)
The purposes of this study were to examine the relationships between dynamic strength index (DSI) and other strength-power performance characteristics and to contextualize DSI scores using case study comparisons. 88 male and 67 female NCAA division I collegiate athletes performed countermovement jumps (CMJ) and isometric mid-thigh pulls (IMTP) during a pre-season testing session as part of a long-term athlete monitoring program. Spearman`s correlations were used to assess the relationships between DSI and CMJ peak force, height, modified reactive strength index, peak power and IMTP peak force and rate of force development (RFD). Very large relationships existed between DSI and IMTP peak force (r = -0.848 and -0.746), while small-moderate relationships existed between DSI and CMJ peak force (r = 0.297 and 0.313), height (r = 0.108 and 0.167), modified reactive strength index (r = 0.174 and 0.274), and IMTP RFD (r = -0.341 and -0.338) for men and women, respectively. Finally, relationships between DSI and CMJ peak power were trivial-small for male (r = 0.008) and female athletes (r = 0.191). Case study analyses revealed that despite similar DSI scores, each athlete`s percentile rankings for each variable and CMJ force-time characteristics were unique, which may suggest different training emphases are needed. Based on the explained variance, an athlete`s IMTP performance may have a larger influence on their DSI score compared to the CMJ. DSI scores should be contextualized using additional performance data to ensure each individual athlete receives the appropriate training stimulus during different training phases throughout the year.